Hygienic and Healthy Lifestyle in the Urban Village of Rangkah Surabaya - Puput Dwi Cahya Ambar Wati; Ilham Akhsanu Ridlo (Universitas Airlangga, 2020)
Background: The Surabaya City Health Office report showed, the coverage of hygienic and healthy lifestyle in 2016 was 75.07%. In Rangkah Village, a total of 2,770 (11.84%) out of 23,390 families were monitored, and as many as 1,552 of them (56.03%) had applied hygienic and healthy lifestyle. Objective: This study identified the relationship between knowledge and attitude with the implementation of clean and healthy lifestyle in Rangkah Village. Method: This study deployed quantitative research with a cross-sectional design. As many as 249 people became the sample selected by using the cluster random sampling. The independent variables were knowledge of and attitudes towards hygienic and healthy lifestyle, while the dependent variable was hygiene and healthy lifestyle. The data were then processed with SPSS to identify whether there is a relationship among the variables observed. Results: Knowledge variable obtained P value of 0.014<α (0.05), meaning there is a relationship of knowledge with hygienic and healthy lifestyle. While attitude variable had P value of 0.082>α (0.05), suggesting that there is no relationship of attitudes with hygienic and healthy lifestyle. Conclusion: One of the factors which greatly influences hygienic and healthy lifestyle in the familiesis knowledge.